Soliton solutions for bogoyavlensky–konoplechenko and jaulent–miodek equations via extended (G'/g)-expansion method - İnç, Mustafa; Kilic, B.; Ugurlu, Y. (Editura Academiei Romane, 2015)
In this paper, we apply the extended (G'/G)-expansion method to construct exact solitary wave solutions, topological solitons, and singular solitons of Bogoyavlensky– Konoplechenko (BK) and Jaulent–Miodek (JM) nonlinear evolution equations. © 2015, Editura Academiei Romane. All rights reserved.
Keywords: Bogoyavlensky–Konoplechenko equation; Extended (G'/G)-expansion method; Jaulent–Miodek equation; Soliton